2008
DOI: 10.1016/j.eatbeh.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat intake among urban, African American adolescents

Abstract: This study examined commonly consumed high-fat food sources to estimate dietary fat intake among 314 urban, African American adolescents (mean age (SD) = 12.57 (.98) years; 66% female; 91% African American non-Hispanic; and 9% African American Hispanic). Youths' fat intake was measured using the Block Fat Screener. Most (77%) participants had diets very high in fat (i.e., 40% to 50% of energy). Mean frequencies of consumption revealed youths' preferences for the following high-fat food items: corn chips, potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…52 While the World Cancer Research Fund/American Institute for Cancer Research argue that there is only limited evidence suggesting that diets high in fats and oils are in themselves a cause of lung and breast cancer, 7 this position is in contrast to those found in earlier studies, which concluded that diets high in fats and oils might be a source of some cancers. 53,54 Indisputably, fats and oils are the most energy-dense constituents of foods and therefore over-consumption could contribute to weight gain, overweight and obesity, which are risk factors for cancer.…”
Section: Discussionmentioning
confidence: 98%
“…52 While the World Cancer Research Fund/American Institute for Cancer Research argue that there is only limited evidence suggesting that diets high in fats and oils are in themselves a cause of lung and breast cancer, 7 this position is in contrast to those found in earlier studies, which concluded that diets high in fats and oils might be a source of some cancers. 53,54 Indisputably, fats and oils are the most energy-dense constituents of foods and therefore over-consumption could contribute to weight gain, overweight and obesity, which are risk factors for cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Black women prefer fried foods more than white women (Dacosta and Wilson, 1996) and African-Americans obtain much of their dietary fat from luncheon meats, bacon and fried poultry (Popkin et al, 2001). In urban, African-American adolescents, there is excessive consumption of fat (Di Noia et al, 2008). These preferences are of concern because polycyclic aromatic hydrocarbons and heterocyclic amines associated with ill-health in humans are formed when meat, chicken and fish are cooked at high temperatures (Weisburger, 2002; WCRF/AICR, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among African American families, multiple factors, including maternal educational achievement; parental dietary patterns and perceptions of child weight status and subsequent health risks; family structure and financial resources; and the degree to which routines, such as engaging in regular family meals, are valued and carried out within the family influence children’s dietary behaviors (Lee et al 2002; Bruss, Morris, and Dannison 2003; Burgess-Champoux et al 2009; Guidetti and Cavazza 2008; Nsiah-Kumi et al 2009). Furthermore, there are racial and ethnic disparities in children’s dietary behaviors, with African American children being less likely to meet grain and dairy intake recommendations and more likely to consume high fat foods and sweetened beverages (Di Noia, Schinke, and Contento 2008; Cullen et al 2002). There is evidence that many of these and other behaviors contributing to unhealthy weight status originate within the home, as children have a tendency to model their parents’ behaviors (Savage, Fisher, and Birch 2007).…”
mentioning
confidence: 99%